Prevalence of von Willebrand disease in the Nordic Region (Hematology Meeting Reports, 2009)
Von Willebrand disease (VWD) encompasses a wide spectrum of disease severity ranging from rare mild bleeding symptoms to severe hemorrhagic episodes that are similar to those of severe hemophilia. Due to this variation, the reported prevalence of VWD is a reflection of the criteria by which patients are identified. There are three subtypes of VWD. In type 1, the von Willebrand factor (VWF) is structurally normal, but has a plasma concentration that is subnormal, thus causing a bleeding diathesis. However, many subjects carrying the trait may have a normal VWF level and no increased bleeding tendency. Thus, type 1 VWD trait includes subjects carrying the hereditary marker who are phenotypically normal. Furthermore, levels of VWF may be low for other reasons than mutations in the VWF gene. It follows that there is a “grey zone” between the sick and the healthy and the definition of VWD type 1 can frequently be questioned.1,2